2021
DOI: 10.1038/s41598-021-97575-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of tear film cytokines in Stevens–Johnson syndrome patients and comparative review of literature

Abstract: To investigate the differential expression of tear cytokine levels among chronic Stevens–Johnson syndrome (SJS) patients to better understand the role of significantly altered cytokines in disease development. Tear samples were collected using Schirmer strips in 24 eyes of chronic SJS, 24 eyes of age and gender-matched controls, and 14 eyes of aqueous deficiency dry eye disease (DED) patients. The cytokine analysis was performed among 18 analytes which include pro-inflammatory, anti-inflammatory factors, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(25 reference statements)
0
7
2
Order By: Relevance
“…Similar to a previous case report [15], our study also found that IL-6 and IL-8 in SJS/TEN patients in the acute phase were signi cantly upregulated. However, unlike the decreased expression of IL-10, TNF-α, and IL-12 in chronic SJS/TEN [11,14], our research showed an increase of such cytokines in the acute disease phase. Even if patients already receive active systemic glucocorticoid and immune globulin therapy, their ocular surface still suffers from a cytokine storm, which represents the organs and tissues that produce tears and palpebral sebum, containing lacrimal glands, accessory lacrimal glands, meibomian glands, ocular surface epithelial cells, and conjunctival goblet cells, all experience a strong immune attack at the very early stage of diseases or even before the onset of ocular symptoms and signs.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Similar to a previous case report [15], our study also found that IL-6 and IL-8 in SJS/TEN patients in the acute phase were signi cantly upregulated. However, unlike the decreased expression of IL-10, TNF-α, and IL-12 in chronic SJS/TEN [11,14], our research showed an increase of such cytokines in the acute disease phase. Even if patients already receive active systemic glucocorticoid and immune globulin therapy, their ocular surface still suffers from a cytokine storm, which represents the organs and tissues that produce tears and palpebral sebum, containing lacrimal glands, accessory lacrimal glands, meibomian glands, ocular surface epithelial cells, and conjunctival goblet cells, all experience a strong immune attack at the very early stage of diseases or even before the onset of ocular symptoms and signs.…”
Section: Discussioncontrasting
confidence: 87%
“…However, no research has yet assessed the ocular surface of acute SJS/TEN patients using conjunctival impression cytology.The pathogenesis of SJS/TEN is not completely clear; it is considered to be a T-cell mediated, delayed hypersensitivity activity, and cytokines play an important role in the development and progression of these diseases [7, 8]. The dynamics of multiple cytokines in the different stages of SJS/TEN were observed in epidermal lesions, blister uid, serum, corneal epithelium, and tears [9][10][11]. As a noninvasive method, tear multi-cytokine analysis helps make an accurate and quantitative assessment of ocular surface in ammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for inflammation is also noticeable through tear film proinflammatory cytokine detection which revealed an increased detection of Interleukin (IL)-1, IL-6, and IL-8 in dry eye patients ( 14 , 15 ). Interestingly in diverse OSID, similar mechanisms of disease and results have been demonstrated, such as presence of these cytokines in tear film of ocular GVHD patients ( 16 ), SJS ( 17 ) and ocular cicatricial pemphigoid (OCP) ( 18 ) compared to normal controls. Data for positive presence of inflammation on these conditions is likewise observable in impression cytology of bulbar and tarsal conjunctiva ( 19 ) and through in vivo confocal imaging of the ocular surface ( 20 ).…”
Section: Introductionmentioning
confidence: 65%
“…Computational and Mathematical Methods in Medicine DED. The proinflammatory factors associated with DED that have been identified in the study are TNFα and IL-1, and CXCL8 is highly expressed in the eyes of patients with chronic dry syndrome [37,38]. MAPK is an important inflammatory target.…”
Section: Discussionmentioning
confidence: 88%